GNSS: crescono i servizi e le nuove applicazioni, ma in parallelo si studiano sistemi alternativi - Marco Lisi (mediaGEO soc. coop., 2021)
GNSS services and new applications are growing but alternative systems are being studied in parallel. Together with their diffusion in all the critical infrastructures of our society, the awareness is growing that the current GNSS constellations (GPS, GLONASS, Galileo and Beidou) are not completely sufficient to guarantee efficient and safe services. "Jamming" and "spoofing" are increasingly real threats. Alternatives, largely based on terrestrial systems, such as E-Loran, or platforms based on the integration of various sensors (for example inertial ones) with GNSS receivers, are in progress to be studied.